Modificação da sílica propiletilenodiamina com formaldeído, estudo do equilíbrio e da cinética de adsorção dos íons cádmio, chumbo e cromato - Aguiar, Franklin Pessoa (2009)
In this work, modified silica gel with the group aminopropiletanoimina was used as retention capacity for the ions cadmium, lead and cromate. The tests were accomplished in aqueous solutions under different conditions of pH, in constant temperature of 298±1 K. The number of mol of the organic chain anchored to the matrix was 0,97mmol /g. The analysis of the curves TG, for the degradation interval between 0,12 and 0,4, shows certain constancy of the value of the activation energy with the increase of the value of the conversion degree, however, the comparison of the activation energies calculated by the method of FWO and by the method of Coats-Redfern shows different results for all the models of simple mechanisms, for that, it is believed that the process in such area conversion doesn't happen through a simple mechanism, but through a complex process where more than one mechanism is acting in the dynamics of the degradation reaction. Based in the number of mols of cadmium, lead and cromate adsorbed, it can settle down the following order: cadmium > cromate > lead. The analysis of the kinetics of the reaction for the three ions shows that the processes of adsorption follow a kinetic law of speed of pseudo-second order with the constants of speed cadmium > lead > cromate. The balance of the process of adsorption is not described by the same model of adsorption; the lead and the cromate are described reasonably well by Langmuir, but for the cadmium it was not found any model to describe the behavior of the process of adsorption satisfactorily.